Detection of Phenolic Compounds by Colorimetric Bioassay Using Crude Polyphenol Oxidase - Gul, I.; Hussain, A.; Sami, A.; Ahmad, Z.; Naqvi, S.M.S.; Ilyas, N.; Ahmad, M. S. (The Nucleus, 2017)
Monitoring of phenolic compounds in food components and industrial processes is of great importance.  Routine analytical techniques used for determination of phenolics are costly and tedious. Enzymatic bioassays can be good alternate due to their inalienable specificity, simplicity and fast responsiveness. The present study was designed to develop a colorimetric bioassay for detection of phenolics using crude extract of polyphenol oxidase (PPO). Crude PPO was extracted from apple and conditions were optimized for enzyme activity. Enzyme was immobilized on solid support (Whatman paper-1 and TLC plate) by over-spotting with 3-mthyl-2-benzothiazolinone hydrazine hydrochloride hydrate (MBTH) to develop bioactive spot. Solutions of four substrates; catechol, 4-methyl catechol, L-3,4-dihydroxyphenylalanine (L-DOPA) and L-tyrosine were independently loaded on bioactive spots where the PPO catalyzed the reaction in which substrate was converted to quinones which formed pink colored adduct with MBTH. Color change was detectable by naked eye but color intensity was determined by image analysis software. The detection limit for catechol, 4- methyl catechol and L-DOPA was 64 ?M, 512 ?M and 4 mM respectively with 5 minutes of response time under optimized conditions (16 enzyme units, 6mM MBTH at pH 7 and 25 °C). The change in color intensity was concentration dependent for each substrate beyond its minimum detection limit. A simple, portable, disposable and low cost colorimetric bioassay was developed for detection of phenolic compounds.